"Life and Debt": Assessing the Impacts of Participatory Housing Reconstruction in Post-Conflict Sri Lanka. Issue 1 (15th August 2016) - Gunasekara, Vagisha; Philips, Mira; Romeshun, Kulsabanathan; Munas, Mohammed
The Owner Driven Housing Assistance (ODHA) scheme is a donor and government supported initiative to help construct housing for internally displaced persons (IDPs) returning to their original areas of residence after the end of the Sri Lankan Civil War in 2009. While ODHA is a commendable initiative for rebuilding the lives of those displaced by war, available evidence indicates an increase in household debt among the beneficiaries of such housing schemes and their vulnerability to livelihood insecurities after resettlement. Based on an analysis of the socio-economic status of ODHA beneficiaries in the northern Sri Lankan districts of Mullaitivu, Kilinochchi and Jaffna, this paper concludes that the financing modality of the housing programme has had a catalytic effect on indebtedness among beneficiaries. An inadequate understanding of the social, economic and cultural contexts that define the lives of beneficiaries on the part of donors and implementers appears to be contributing to unintended and negative repercussions of housing assistance. This paper illustrates how post-war participatory development projects such as the ODHA scheme can further exacerbate the vulnerability of war-affected populations, unless donors and policy makers have a holistic understanding of the varying contexts that define the experiences of those receiving development assistance.